Active exoskeleton reduces erector spinae muscle activity during lifting - Walter, Tobias; Stutzig, Norman; Siebert, Tobias (Frontiers in Bioengineering and Biotechnology, 2023)
Musculoskeletal disorders (MSD) are a widespread problem, often regarding the lumbar region. Exoskeletons designed to support the lower back could be used in physically demanding professions to reduce loading of the musculoskeletal system, e.g., by lowering lifting task related muscle activation. The present study aims to investigate the effect of an active exoskeleton on back muscle activity when lifting weights. Within the framework of the study, 14 subjects were asked to lift a 15 kg box with and without an active exoskeleton which allows the adjustment of different levels of support, while the activity of their M. erector spinae (MES) was measured using electromyography. Additionally, the subjects were asked about their overall rating of perceived exertion (RPE) during lifting under various conditions. Using the exoskeleton with the maximum level of support, the muscle activity was significantly lower than without exoskeleton. A significant correlation was found between the exoskeleton's support level and the MES activity. The higher the support level, the lower the observed muscle activity. A reduction in the activity of the erector spinae indicates actual support for the movement task set and might indicate lower compression forces in the lumbar region. Furthermore, when lifting with the maximum level of support, RPE was found to be significantly lower than without exoskeleton too. It is concluded that the active exoskeleton supports people noticeably when lifting heavy weights. Exoskeletons are a powerful tool for reducing load during physically demanding jobs and thus, their use might lower the risk of MSD.